DESAIN MOCKUP APLIKASI URCARE MENGGUNAKAN DESIGN THINKING - Diva Destia Rohyadi; Tiawan Tiawan; Zia Imam Perdana; Lila Setiyani; Muhammad Fajar Ramadhan; Muhammad Hanif Solatan; Kristian Maulana; Rini Ayu Parwati; Rheisya Vascahalia Putri (Jurnal Informatika Teknologi dan Sains (Jinteks), 2024)
In this research, the problem that arises is that when the community creates an initial mockup design for the URCare application which aims to help with community emergencies so that the community can report incidents in real time to the BPBD (Regional Disaster Management Agency), the application design is created using the design thought method which produces The output is in the form of a prototype that is in accordance with the needs of emergency problems that arise in the community. It is hoped that this design plan can make it easier for developers to create applications that provide fast service access with relevant and precise information so as to ensure that information can be conveyed between users, in this case the community and The party receiving emergency information and with design thought is expected to provide an effective and efficient approach in making mockup designs.